2014
DOI: 10.1007/s12149-014-0874-1
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of mid- and post-treatment [18F]fluorodeoxyglucose (FDG) positron emission tomography (PET) in indolent follicular lymphoma

Abstract: Post-treatment PET is predictive of OS in indolent FL. It identifies patients who might benefit from more intensive follow-up, enrolment in clinical trials or second-line therapy. Mid-treatment PET scan results did not appear to predict long-term treatment outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“… FLIPI score d Treatment regimes (no.) Lu et al [ 6 ] (2014) Australia Retrospective 57 59 b (27–77) 26/31 I, 3 II, 7 III, 24 IV, 21 0, 2 1, 9 2, 19 3, 11 4, 8 5, 4 Unavailable, 4 6× R-CHOP, 57 Additional maintenance R, 45 Luminari et al [ 7 ] (2014) Italy Retrospective 202 56 b (33–75) 98/104 II, 16 III/IV, 186 0–2, 131 3–5, 71 R-CVP, 66 R-CHOP, 62 R-FM, 74 Zinzani et al [ 8 ] (2013) Italy Retrospective 142 63 a (25–83) 55/87 III, 65 IV, 77 NR R-FM Dupuis et al [ 9 ] (2012) Multinational Prospective 119 57 b (28–76) 63/56 I/II, 8 III/IV, 110 0–1, 17 2, 50 3–5, 49 6× R-CHOP, 113 2× additional R, 106 Trotman et al [ 10 ] (2011) Multinational Prospective 122 57 b (26–82) 67/55 I/II, 14 III/IV, 108 0–1, 28 2, 47 3–5, 47 6× R-CHOP + 2× R, 103 8× R-CVP, 19 Le Dortz et al [ 11 ] (2010) France Retrospective 45 60 a (47–78) 22/23 I/II, 5 III, 15 IV, 25 0–1, 9 2, 12 3–5, 24 6× R-CHOP Bishu et al [ 12 ] (2007) USA Retrospective …”
Section: Resultsmentioning
confidence: 99%
“… FLIPI score d Treatment regimes (no.) Lu et al [ 6 ] (2014) Australia Retrospective 57 59 b (27–77) 26/31 I, 3 II, 7 III, 24 IV, 21 0, 2 1, 9 2, 19 3, 11 4, 8 5, 4 Unavailable, 4 6× R-CHOP, 57 Additional maintenance R, 45 Luminari et al [ 7 ] (2014) Italy Retrospective 202 56 b (33–75) 98/104 II, 16 III/IV, 186 0–2, 131 3–5, 71 R-CVP, 66 R-CHOP, 62 R-FM, 74 Zinzani et al [ 8 ] (2013) Italy Retrospective 142 63 a (25–83) 55/87 III, 65 IV, 77 NR R-FM Dupuis et al [ 9 ] (2012) Multinational Prospective 119 57 b (28–76) 63/56 I/II, 8 III/IV, 110 0–1, 17 2, 50 3–5, 49 6× R-CHOP, 113 2× additional R, 106 Trotman et al [ 10 ] (2011) Multinational Prospective 122 57 b (26–82) 67/55 I/II, 14 III/IV, 108 0–1, 28 2, 47 3–5, 47 6× R-CHOP + 2× R, 103 8× R-CVP, 19 Le Dortz et al [ 11 ] (2010) France Retrospective 45 60 a (47–78) 22/23 I/II, 5 III, 15 IV, 25 0–1, 9 2, 12 3–5, 24 6× R-CHOP Bishu et al [ 12 ] (2007) USA Retrospective …”
Section: Resultsmentioning
confidence: 99%
“…At the heart of every comparison between the two methods is the trade-off between how early in the course of treatment a PET/CT scan is acquired and how accurate its predictions will be. This phenomenon is exemplified by studies in which end-of-treatment imaging was successful in significantly predicting outcomes but interim imaging was not (15,39,40). However, the difference in accuracy between interim and endof-therapy results has been marginal in many cases (38) and is often outweighed by the tremendous advantages of gleaning information as early as possible to determine whether to stay the course of treatment or change the management strategy.…”
Section: Resultsmentioning
confidence: 99%
“…These studies are highly varied in methodology, but they consistently corroborate the reliability of end-of-treatment imaging. Similar to HL, studies of NHL have shown that even when interim imaging fails to significantly distinguish between patients, posttreatment PET is reliably prognostic (39,40).…”
Section: End-of-treatment Response Asssessment In Nhlmentioning
confidence: 99%
“…Only three out four studies comparing OS and PET results showed a strict association, with a significantly lower survival in patients with a positive scan. Curiously in one single study38 only a trend toward significance was found between 3-Y PFS and scan results, with a PFS of 74.4% and 38.2% for PET-negative and positive patients, respectively (p=0.083). In the same study FDG-PET was predictive of OS, showing mean OS of 95.2 and 45 months in PET-negative and positive patients, respectively (p<0.001).…”
Section: Fdg-pet For Treatment Response Evaluation In Flmentioning
confidence: 95%